What Drives the Reversal of Gender Disparity in Higher Education Instituitions (HEIs): A Critical Review - Sultana, A. M (International Journal of Psychosocial Rehabilitation, 2020)
Over the past two decades, female participation in higher education has increased tremendously. In many industrialized the educational attainment of females now often exceeds that of males. Women’s participation in HE, relative to men’s, has increased, especially in Western Europe and North America. Across the EU, women constitute about half (46%) of all PhD graduates and their rate of increase from 2002 to 2010 was more than twice that of their male counterparts. The international literature mainly focuses on changing gender patterns in tertiary education. The literature on the existence of explanations for gender imbalances in higher education (HE) focusing particularly on girls’ increasing access to HEIs. It is an urgent need to understand the barriers that discourage or hinder students from progressing into higher education in across HEIs. The paper attempts to demonstrate the extent of the gender gap in higher education across different HEIs. More specifically, the paper investigates the factors behind the reversal of the gender disparity in tertiary education from Malaysia and other Western country’s perspectives.